Upaya Perbaikan Penanganan Anggur (Vitis vinifera L. Var. Alphonso lavallee) dalam Distribusinya dari Petani Desa Kalianget Buleleng ke Denpasar - Sriani, Ni Kadek; Harsojuwono, Bambang Admadi; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): SeptemberDO - 10.24843/JRMA.2020.v08.i03.p07, 2020)
Efforts to improve are expected to minimize the damage to grapes during the distribution process . The aims of this study w ere to find out the number channel and the distribution of grape from farmers of Kalianget Village on Buleleng to Denpasar, to determine the handling of grape in distribution and to analysis the impact of postharvest repairs on grape damage from farmers of Kalianget Village on Buleleng to Denpasar with improve ment treatment replacement and addition of packaging materials in the form of plastic containers, the addition of PE plastic films and pieces of paper. The method used to determine the distribution lines is the snowball sampling method in the form of surveys and interviews with the Commodity System Assessment Method (CSAM) . There are four lines in the distribution, that is line I (Farmer - Middleman - Retailer - Consumer), line II (Farmer - Middleman - Restaurant - Consumer), line III (Farmers - Middleman - Wholesaler - Retailer - Consumer) and line IV (Farmer - Middleman - Wholesaler - Wine Industry - Consumer). Postharvest improvement w as carried out on the distribution channel which have the most loss, namely on line I with a percentage of damage of 3.90%. Postharvest handling from the farmer to the retailer includes the process of harvesting, sorting, weighing, packaging, storage, distribution and displaying. The impact of handling postharvest loss of grape on the sorting process at the farm level is 1.81% (non significant), middleman level is 1.13% (non significant), wholesaler level is 2.41% (non significant) and retailer level is 8.36% (significant). Improvement efforts made can reduce the level of loss in grape. Replacement and addition of grape packaging materials in the form of PE plastic film , pieces of paper and the use of plastic container can reduce the percentage of damage which is 7.5%. Keywords : Grape, packaging, postharvest, CSAM, handling improvements